The Influence of Transformational Leadership Style on Employee Performance Through Work Motivation and Organizational Culture as Mediating Variables - Lango, Rikardus Kurnia; Sopiah, Sopiah; Syihabudhin, Syihabudhin (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2024)
This research was conducted at the Aria Group Hotel to determine the application and influence of the Transformational Leadership Style on Employee Performance through Work Motivation and Organizational Culture as mediating variables in Hotel Aria Group. This research uses quantitative methods with explanatory research type. There are 4 types of variables in this research, namely Transformational Leadership Style, Work Motivation, Organizational Culture, and Employee Performance. The number of respondents in this study was 107 respondents. This sampling technique uses proportionate random sampling. The analysis techniques for this research are statistical analysis and Path Analysis. The results of this research indicate that the Transformational Leadership Style does not affect Employee Performance but has a positive and significant effect on Work Motivation and Organization Culture. Work Motivation and Organizational Culture can mediate the influence of Transformational Leadership Style on Employee Performance. The contribution of these findings can help management map the problems that exist within the company so that they can carry out maximum evaluations. Leaders are advised to also develop programs that support their efforts to improve the competence of their employees, and leaders also consider using the good input that has been proposed. by its employees to improve organizational performance.